In Defence of Labour Market Institutions Cultivating Justice in the Developing World - Berg, Janine; Kucera, David (Palgrave Macmillan UK, 2008)
Though labour market regulations have been blamed for the poor economic performance of many developing countries, the evidence on which this argument rests is weak. Through a survey of different labour market institutions in developing countries, this book reaffirms the importance of labour market institutions in this era of globalization
Keywords: Labor economics; Development economics